Argumentative analysis of autobiographical recounts of institutional violence suffered by Chilean women with a diagnosis of endometriosis - Díaz, Natalia (2023)
This article delves into the link between discourse and health. The objective of study is examining the experiences of institutional violence that patients with endometriosis have suffered through the analysis of the argumentation. The methodological framework is eminently qualitative. The corpus consists of thirty semi-structured interviews with Chilean women with diagnosed endometriosis. The argumentative schemes (Toulmin, 1958; Pardo, 2011 and Molina, 2012) present in the autobiographical accounts of these women when they deal with an episode of institutional violence suffered are analyzed. The results show that both the data and the conclusions are based on facts experienced by the patients in their interactions with their doctors or the public health care system, who represent the most frequent social actors in these stories. In addition, the guarantees exposed show social beliefs that hinder the doctor-patient relationship. This allows us to conclude how episodes of violence are repeated in clinical practice, which further exposes these patients to new ailments.